Kajian Etnopedagogi Upacara Beberkatan Di Desa Adat Bestala Kecamatan Seririt Kabupaten Buleleng - Gede Sugiyastika; I Made Suweta; I Putu Gede Parmajaya (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2023)
The beberkatan ceremony is one form of the implementation of yadnya carried out from generation to generation by Hindus in the Bestala Traditional Village, Seririt District, Buleleng Regency. This ceremony is very unique because this ceremony is carried out at a certain time. The beberkatan ceremony is carried out as a form of gratitude to Sangkara. This study aims to find out: (1) the myth contained in the beberkatan ceremony, (2) the procession of the beberkatan ceremony in the Bestala Traditional Village, (3) the ethno paedagogic value contained in the beberkatan ceremony in the Bestala Traditional Village. The myth contained in the beberkatan ceremony, is a ritual ceremony that is carried out when all the tanem tuwuh trees bear fruit heavily or great harvest. This beberkatan ceremony is based on beliefs of the existence of bala samar. This beberkatan ceremony is also a form of gratitude for Ida Sang Hyang Widhi Wasa's grace in his manifestation as Lord Sangkara who controls the plants. The procession of the beberkatan ceremony begins with preparing reramon, matur piuning, asking for holy water, mereresik, pengastawa penganteb, offering caru, praying together, ngerauhang procession, and closing. The etnho pedagogic values contained in the beberkatan ceremony in the Bestala Traditional Village are the value of religious education, the value of ethical education, the value of social education, and the value of environmental preservation educational.